Efficacy of banana plantlet production by micropropagation - Mendes, Beatriz M. J.; Mendes, Fernanda J.; Neto, Augusto Tulmann; Demetrio, Clarice G. B; Puske, Otto Ricardo (Pesquisa Agropecuaria Brasileira, 1996)
The use of banana (Musa spp.) plant production by tissue culture is increasing throughout the world. However the occurrence of somaclonal variation has been one of the most important problems affecting the commercial value of the plants. A reason for the somaclonal variation can be the time of permanence of the culture in vitro, i.e., the number of subcultures. With the aim of evaluating the effectiveness of banana plant production from shoot tip in vitro, and the behavior of vegetative apices coming from different rhizomes of cv. Nanicio, nine shoot tips were cultured in MS medium supplemented with 4.5 mg/L BAP for six subcultures at fourweek intervals. The evaluations were done at each subculture by counting the number of new shoots produced. The results show that shoot tips coming from different rhizomes behave differently under in vitro conditions, some being highly productive and others producing a much smaller number of plants under similar culture conditions. The average number of plants produced was 676 per shoot tip after six subcultures, with 1,850 plants produced by the most productive, against 143 plants produced by the lowest productive one. These data can be very useful for micropropagation companies in the screening of the most promissor shoot tips in the beginning of the culture and in the economic calculations of the individual plantlets prices.